2018
DOI: 10.1017/s136898001800099x
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices and determinant variables for early complementary feeding in the first 8 months of life: results from the Brazilian MAL-ED cohort site

Abstract: ObjectiveThe present study aimed to describe breast-feeding, complementary feeding and determining factors for early complementary feeding from birth to 8 months of age in a typical Brazilian low-income urban community.DesignA birth cohort was conducted (n 233), with data collection twice weekly, allowing close observation of breast-feeding, complementary feeding introduction and description of the WHO core indicators on infant and young child feeding. Infant feeding practices were related to socio-economic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
4
21
1
3
Order By: Relevance
“…Several studies show that the exposure to a greater variety of flavors, during breastfeeding, can facilitate the acceptance of new foods during complementary food introduction and it is also expected that breastfeeding mothers will be more likely to encourage healthy foods consumption [1,14,15]. Still, some studies relate healthy feeding indicators to other socioeconomic factors, including income and education [4,32], which might play a more important role in our study when compared to breastmilk intake.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies show that the exposure to a greater variety of flavors, during breastfeeding, can facilitate the acceptance of new foods during complementary food introduction and it is also expected that breastfeeding mothers will be more likely to encourage healthy foods consumption [1,14,15]. Still, some studies relate healthy feeding indicators to other socioeconomic factors, including income and education [4,32], which might play a more important role in our study when compared to breastmilk intake.…”
Section: Discussionmentioning
confidence: 91%
“…During the first 1000 days of life following birth, healthy feeding practices are associated with the reduction of morbidity and mortality in childhood [1]. During the first 6 months of life, breastmilk is enough to supply all of the child's nutritional requirements and after this period, breastfeeding, along with opportune and adequate complementary feeding, contribute to establishing healthy eating habits and are related to repercussions for lifetime health [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are comparable with previous studies. In Northeast Brazil, a birth cohort study showed that 96•7 % of the children receive any liquid, semi-solid or solid before 6 months of age (3) . Likewise, in the Southampton Women's Survey from UK, 95 % of the mothers introduced solid foods to their infants before 6 months of age (27) .…”
Section: Discussionmentioning
confidence: 99%
“…IYCF practice was associated with the household's financial resources (Ahishakiye et al, 2019;Helle, Hillesund, & Overby, 2018;G. N. Khan et al, 2017;Maciel et al, 2018;Na, Aguayo, Arimond, Narayan, & Stewart, 2018b) and urban-rural location (Nguyen et al, 2018;Tassew et al, 2019). It implies that wealth and living in urban areas determine the ease of accessing resources to meet child's adequate feeding practice.…”
Section: Discussionmentioning
confidence: 99%